IMPACT OF INSTAGRAM AND YOUTUBE INFLUENCERS ON CONSUMER BEHAVIOUR IN DELHI NCR - Vandana, .; Komal, . (INTI International University, 2023)
This study investigates the influence of YouTube and Instagram influencers on consumer behaviour in Delhi-National Capital Region, India. The study seeks to assess the relative impact of Instagram and YouTube marketing components in terms of establishing brand value and consumer preferences. It also attempts to examine the primary components of brand equity generation through Influencer marketing, as well as to comprehend the impact of influencer marketing and brand equity on brand loyalty, brand preference, and brands' ability to charge a premium price for the products. Purposive sampling techniques with a convenience sampling methodology were used to select 100 respondents for the study. Respondents must be between the ages of 17 and 35, live in India, and use Instagram and YouTube. SPSS 26 was employed as the analytical tool in this investigation. According to the results, Instabloggers & YouTubers are regarded as trusted sources of information by customers. Furthermore, positive YouTube reviews & Instagram photos influence consumer purchase decisions.